2019
DOI: 10.3389/fpls.2019.01120
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens and Molds Affecting Production and Quality of Cannabis sativa L.

Abstract: Plant pathogens infecting marijuana (Cannabis sativa L.) plants reduce growth of the crop by affecting the roots, crown, and foliage. In addition, fungi (molds) that colonize the inflorescences (buds) during development or after harvest, and which colonize internal tissues as endophytes, can reduce product quality. The pathogens and molds that affect C. sativa grown hydroponically indoors (in environmentally controlled growth rooms and greenhouses) and field-grown plants were studied over multiple years of sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 46 publications
6
114
0
4
Order By: Relevance
“…The distinguishable clades are represented by letters from A to C. the frequency of cuttings taken at this distance that showed recovery of F. oxysporum was about 0.5%. The pith tissues in cannabis plants could allow spread of potential pathogens such as F. oxysporum to occur, as demonstrated previously for endophytic fungi (Punja et al 2019a). The ability of F. oxysporum to colonize exposed pruning wounds from airborne inoculum and spread into the pith tissues could also provide opportunities for internal colonization of cannabis plants.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The distinguishable clades are represented by letters from A to C. the frequency of cuttings taken at this distance that showed recovery of F. oxysporum was about 0.5%. The pith tissues in cannabis plants could allow spread of potential pathogens such as F. oxysporum to occur, as demonstrated previously for endophytic fungi (Punja et al 2019a). The ability of F. oxysporum to colonize exposed pruning wounds from airborne inoculum and spread into the pith tissues could also provide opportunities for internal colonization of cannabis plants.…”
Section: Discussionmentioning
confidence: 72%
“…Among several challenges currently facing cannabis producers, management of diseases remains a high priority. Many of the recently reported diseases that affect cannabis production in Canada, such as root and crown rots, powdery mildew, and bud rots caused by Botrytis and Penicillium species, are appearing in both indoor controlled environment facilities and greenhouse production (Punja et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Medical, as well as recreational Cannabis grown in indoor facilities is exposed to a plethora of microbial contaminants occurring on pre-and post-harvest Cannabis inflorescence buds. The literature addresses an extensive list of fungal and bacterial contaminants, as well as of associated toxins, on Cannabis [20,[46][47][48]. Taken together, published results confirm that viable organisms, including those that produce mycotoxins and endotoxins, can be recovered from Cannabis, potentially posing a serious risk to immunosuppressed individuals [48].…”
Section: Indoor Cultivation and Storage Of Cannabis Are Propitious Tomentioning
confidence: 68%
“…Cannabis inflorescence buds are often contaminated with molds and mycotoxins [46], particularly if not stored properly [50]. Methods for controlling mycotoxins are mostly preventive during production, handling, transportation, storage, and processing [51,52].…”
Section: Indoor Cultivation and Storage Of Cannabis Are Propitious Tomentioning
confidence: 99%
“…The patient elected to discontinue treatment and passed two weeks after transitioning to hospice care (Dehal and Quimby, 2019). There are limited case studies demonstrating Cannabis causing Fusariosis; however, there are a plethora of studies that have found Fusarium to be in direct relationship with Cannabis (Mcpartland and Hillig, 2004;Punja et al, 2019).…”
Section: Case Studymentioning
confidence: 99%